Reproductive ecology of the island scrub-jay (Aphelocoma insularis) - Caldwell, Luke, author; Angeloni, Lisa M., advisor; Sillett, T. Scott, committee member; Savidge, Julie A., committee member (Colorado State University. Libraries, 2010)
The small population size and limited range of the Island Scrub-Jay make it a species of conservation concern, yet its reproductive ecology is poorly known. From 2008 - 2010 I investigated factors influencing nest success, quantified annual fecundity per pair, and documented breeding behavior. Nest predation was the major factor influencing nest success, accounting for 92 percent of documented nest failures. Nests that were initiated earlier in the breeding season, nests that were higher and more concealed, and nests of breeding pairs that had smaller home ranges had higher daily nest survival. Despite a low estimated daily nest survival rate of 0.945 ± 0.004 SE, the high frequency of renesting allowed pairs to maintain a mean fecundity of 1.13 ± 0.15 SE. Island Scrub-Jays may benefit from an increase in breeding habitat and lower nest predation from the ongoing regeneration of woody vegetation and understory structure following the removal of exotic herbivores on Santa Cruz Island.
Keywords: nest success; nest predation; island scrub-jay; habitat-specific fecundity; Santa Cruz Island; Island scrub jay -- California -- Santa Cruz Island -- Reproduction; Island scrub jay -- Ecology -- California -- Santa Cruz Island; Aphelocoma insularis